SYNTHESIS AND BIOLOGICAL EVALUATIONS OF N-(2-SUBSTITUTED-1-CARBOXYL) VINYLAZETIDINONES - A STUDY ON THE ESSENTIAL STRUCTURAL ELEMENT FOR BIOLOGICAL-ACTIVITIES OF BETA-LACTAM ANTIBIOTICS - KANG, HY; PAE, AN; KOH, HY; CHANG, MH (KOREAN CHEMICAL SOC, 1991)
A series of compounds, N-(2-substituted-1-carboxy)vinylazetidinones were successfully synthesized in order to test the hypothesis that biological activities of beta-lactam antibiotics could be attributed to the smooth flow of electrons after a nucleophilic attack at the carbonyl carbon in the beta-lactam ring. After introduction of aminothiazolylacetamido group at 3-position of the azetidinones, their biological activities were evaluated. Their low activities led to the conclusion that the smooth electron flow in beta-lactams in not the sufficient source for the biological activities.
Keywords: LACTIVICIN; PENEMS